Qualidade de vida no trabalho: um estudo de caso com servidores de uma instituição federal de ensino superior - Orsiolli, Thamella Hellen Estefanuto (2023)
The objective of this work is to analyze the perception of public servants of the Federal University of Latin American Integration (UNILA) in relation to their quality of life at work (QVT). Therefore, an applied, exploratory and descriptive research was outlined, being a case study with a quantitative approach. For data collection, a closed structured questionnaire was used, survey style, with a five-point Likert scale, called Quality of Working Life Questionnaire-Bref (QWLQ-Bref). The sample was of the non-probabilistic type and consisted of 247 federal civil servants, including the category Teacher and Administrative Technician in education (TAE). In the data analysis, it was identified as to the profile of the respondents, most of them female, aged between 31 and 40 years, with specialization, level D position, with 7 to 9 years of service in the institution, in face-to-face work and do not occupy leadership position. Regarding the level of QWL, the Physical/Health, Psychological, Personal and Professional domains and the total QWL index were evaluated. All of these obtained indices considered satisfactory, with higher and lower grades respectively in the personal and professional domains, demanding greater attention from the institution regarding the latter. Crossing the data also showed a moderate relationship between the capacity sector and the server's QWL perception. The addition of two questions to the form indicated that, in the respondents' perception, the activities carried out have a greater positive than negative influence on QWL. The limitations of this work involve the limited time, not allowing the crossing of new data, which would culminate in new results. Finally, the practical contributions of this work to UNILA include the diagnosis of QWL, identifying the level of satisfaction, information on influencers in the QWL of employees, which can support the institutional decisionmaking process. As for the Public Administration, they help policymakers in making decisions related to QWL in the public service. With regard to theoretical contributions, greater understanding of QWL and its areas of study is mentioned; in the dissemination of the theme in a public context; understanding of a QWL assessment instrument and information that may support other studies.